Fully scalable intraband coding of wavelet-decomposed 3D meshes - Denis, L.; Satti, S.M.; Munteanu, A.; Cornelis, J.; Schelkens, P. (2009 16th International Conference on Digital Signal Processing, 2009)
In this paper, a scalable intraband wavelet coding technique for semi-regular topology surface meshes is proposed. The choice of an intraband codec design is justified through an information theoretic analysis of the statistical dependencies between the wavelet coefficients resulting from a wavelet-based decomposition of the input 3D mesh. The bitstream produced by the proposed codec is both resolution and quality scalable. This lies in contrast with well-known zero-tree based interband coding techniques that only support quality scalability. The experimental results show that, on average, the proposed codec outperforms the state-of-the-art zero-tree based interband codec in rate-distortion sense when using the L 2 norm as target distortion metric.